Association of serum magnesium levels with risk factors, severity and prognosis in ischemic and hemorrhagic stroke patients - Samavarchi Tehrani, Sadra (Caspian J Intern Med, 2020)
BACKGROUND: Stroke is the third leading cause of mortality worldwide. One of the factors that affect the occurrence of stroke can be attributed to changes in the levels of trace elements. Accumulating evidence has been shown that magnesium, as an important element, is a new predictor of stroke. We aimed to determine the levels of Mg in ischemic stroke patients in comparison with those having the hemorrhagic type. METHODS: This study was conducted on 447 stroke patients. Demographic characteristics of patients, stroke severity, and risk factors such as hypertension, ischemic heart disease, diabetes mellitus, and hyperlipidemia were recorded. Stroke was diagnosed based on the neurological examination and neuroimaging findings e.g. computed tomography (CT) or magnetic resonance imaging (MRI). The colorimetric technique was used to determine the concentration of Mg at 450 nm according to the commercial kit. RESULTS: The mean of magnesium levels in ischemic patients was significantly higher than that in the hemorrhagic patients (P=0.001). Difference in magnesium status was associated with gender in thrombotic patients (P<0.05), while hyperlipidemia was associated with the status of magnesium in embolic patients (P=0.012). Furthermore, magnesium levels were correlated with ischemic heart disease in embolic (P=0.011) and sub-arachnoid hemorrhagic (SAH) patients (P=0.012), and with diabetes mellitus in thrombotic patients (P=0.012). Magnesium status was associated with the severity of ischemic stroke at the time of discharge in ischemic patients (P<0.001). Mg levels had the best area under curve (AUC) for the discrimination of ischemic patients from hemorrhagic ones. CONCLUSION: Magnesium levels were higher in ischemic patients compared to hemorrhagic ones, and these levels were associated with many risk factors contributing to a stroke. Magnesium may be used as a new predictor of stroke in ischemic patients as opposed to hemorrhagic ones.